2003
DOI: 10.1180/0026461036740129
|View full text |Cite
|
Sign up to set email alerts
|

Al-rich diopside in alluvial ruby and corundum-bearing xenoliths, Australian and SE Asian basalt fields

Abstract: Alluvial rubies and sapphires are found in palaeodrainage deposits along the Cudgegong-Macquarie River system, central eastern New South Wales, Australia. A pink to red suite contains Cr (up to 0.6 wt.% Cr2O3) as the main chromophore, exceeding Fe (up to 0.5 wt.%Fe2O3). Corrosive etching suggests a prior xenocrystic Mesozoic-Cenozoic basaltic transport, while Cr2O3/Ga2O3to Fe2O3/TiO2ratios indicate an original metamorphic source. Syngenetic mineral inclusions include Al-rich diopside, meionite and anatase. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Nevertheless, the associations of corundum together with clinopyroxene and garnet (Sobolev et al, 1998) or Alrich clinopyroxene have been identified in diamond (Hutchinson et al, 2001(Hutchinson et al, , 2004 as well as in corundum (Saminpanya and Sutherland, 2011;Sutherland et al, 2003;Sutthirat et al, 2001). At the Juina kimberlite deposit, high Cr 2 O 3 ruby inclusions in diamond are associated with Al-rich pyroxene (up to 10 wt% Al 2 O 3 ), ferropericlase and Mg-perovskite (Hutchinson et al, 2001).…”
Section: The Rubies Of Mbuji-mayimentioning
confidence: 96%
“…Nevertheless, the associations of corundum together with clinopyroxene and garnet (Sobolev et al, 1998) or Alrich clinopyroxene have been identified in diamond (Hutchinson et al, 2001(Hutchinson et al, , 2004 as well as in corundum (Saminpanya and Sutherland, 2011;Sutherland et al, 2003;Sutthirat et al, 2001). At the Juina kimberlite deposit, high Cr 2 O 3 ruby inclusions in diamond are associated with Al-rich pyroxene (up to 10 wt% Al 2 O 3 ), ferropericlase and Mg-perovskite (Hutchinson et al, 2001).…”
Section: The Rubies Of Mbuji-mayimentioning
confidence: 96%
“…The Macquarie River ruby grades into pink sapphire and its source region is poorly constrained, as stones were recovered as accessories in gold dredging operations in the alluvial river bed. It accompanies diamonds and represents a distinctive highly Mg-rich, high temperature genetic type [47]. The New England ruby is a rare accessory in gem field workings within the dissected Maybole shield volcano sequences [48].…”
Section: Local and Geological Settings East Australiamentioning
confidence: 99%
“…Photos of ruby features from Macquarie-Cudgegong River system alluvial deposits, NSW (a) ruby fragment, a few mm across with pyrope garnet inclusion (center). (b) Facetted stones of ruby and pink sapphire, up to 3 mm across[47]. Photographer G. Webb, Australian Museum.…”
mentioning
confidence: 99%
“…In the case of Australian basaltrelated corundum, the conditions required for formation are enigmatic: corundum crystals have mineralogical associations suggesting a wide range of pressure, temperature and geochemical conditions during their generation (e.g. Sutherland and Coenraads, 1996;Sutherland et al, 2003;Zaw et al, 2006). In eastern Australia, sapphires and rubies seem to have been transported to the surface as xenocrysts in alkali basalts (see Table 1), but they are also found in xenoliths in rare instances (Sutherland et al, 2003(Sutherland et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%